1994
DOI: 10.1016/0020-7292(94)90081-7
|View full text |Cite
|
Sign up to set email alerts
|

Are war and public health compatible?

Abstract: The term reflection has been been used to describe a form of re-entry in a linear bundle in which two regions of excitable tissue are separated by an area of depressed conduction.4 During reflection, excitation occurs slowly in one direction along the bundle and is followed by continued propagation and excitation in the opposite direction. One form of reflection may be micro re-entry due to functional longitudinal dissociation within the depressed segments Parasystole An ectopic pacemaker may sometimes be conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Toole et al reported detailed assessments of the public health consequences of the war in Bosnia and Herzegovina. 13 Also, Acheson 14 recently reviewed humanitarian relief efforts and health assessments by the WHO in Bosnia and Herzegovina, and Kuzman et al 15 recently reviewed causes of death in the war in Croatia. International humanitarian relief efforts in Sarajevo have not kept-up with the emergency care needs of the civilian population.…”
Section: Discussionmentioning
confidence: 99%
“…Toole et al reported detailed assessments of the public health consequences of the war in Bosnia and Herzegovina. 13 Also, Acheson 14 recently reviewed humanitarian relief efforts and health assessments by the WHO in Bosnia and Herzegovina, and Kuzman et al 15 recently reviewed causes of death in the war in Croatia. International humanitarian relief efforts in Sarajevo have not kept-up with the emergency care needs of the civilian population.…”
Section: Discussionmentioning
confidence: 99%
“…Many worked in hospitals often subjected to rocket attacks. They witnessed war atrocities, risked personal safety when working on military bases, and experienced aggravated sexual exploitation and environmental degradation (Geiger, 2000;Toole, Galson, & Brady, 1993). The phenomenon of war and its psychological aftermath may differentially affect their lives for many years.…”
Section: Introductionmentioning
confidence: 98%
“…Public health activities are difficult during a war, but often possible in areas where there is no active fighting or confrontation (Armenian, 1986;Toole et al, 1993;Healing et al, 1996). The survey reported here showed that a technique which had proved itself in the aftermath of a natural disaster (Hlady et al, 1994) was also useful in a war zone although further work is necessary to make it more user friendly.…”
Section: Redirecting Merlin's Activitiesmentioning
confidence: 83%